(untitled) (Dissertare, 2021)
The objective of this article is to review the literature on the study of capital structure in Peruvian companies, with an emphasis on small and medium-sized companies. This highlights the findings regarding the determinants of the aforementioned structure and the sources of financing used predominantly by these companies. Likewise, there are challenges for the investigation of this subject within the scope of Peruvian SMEs, within the framework of the theories on capital structure. The study carried out has a documentary design, with a descriptive level and based on bibliographic review techniques. In conclusion, it is highlighted that research on the capital structure of small and medium-sized Peruvian companies is scarce and their findings are not totally consistent with each other, nor with the rest of the literature, since it basically corroborates the importance of the size of the company as a determinant of the capital structure. Due to the aforementioned, it is necessary to expand the number of investigations to validate the existing empirical evidence and analyze new variables, such as the activity sector, the formality and legal status of the companies, as well as macroeconomic factors.